2004
DOI: 10.1111/j.1365-201x.2004.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Volume natriuresis vs. pressure natriuresis

Abstract: Body fluid regulation depends on regulation of renal excretion. This includes a fast vasopressin-mediated water-retaining mechanism, and slower, complex sodium-retaining systems dominated by the renin-angiotensin aldosterone cascade. The sensory mechanisms of sodium control are not identified; effectors may include renal arterial pressure, renal reflexes, extrarenal hormones and other regulatory factors. Since the pioneering work of Guyton more than three decades ago, pressure natriuresis has been in focus. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 36 publications
(68 reference statements)
1
53
1
2
Order By: Relevance
“…Investigators from Odense and Berlin have argued that the pressure natriuresis mechanism is not always operative during modest changes in arterial pressure. 19,20 In regard to the present study, if this interpretation were correct, and the concomitant neurohumoral responses did not enhance pressure natriuresis, this would indicate that renal excretory function adapts to changes in arterial pressure and that reductions in either cardiac output or peripheral resistance could be causal mechanisms that account for long-term reductions in arterial pressure during prolonged baroreflex activation. Additional long-term studies are needed to provide greater insight into this controversy.…”
Section: Discussionmentioning
confidence: 94%
“…Investigators from Odense and Berlin have argued that the pressure natriuresis mechanism is not always operative during modest changes in arterial pressure. 19,20 In regard to the present study, if this interpretation were correct, and the concomitant neurohumoral responses did not enhance pressure natriuresis, this would indicate that renal excretory function adapts to changes in arterial pressure and that reductions in either cardiac output or peripheral resistance could be causal mechanisms that account for long-term reductions in arterial pressure during prolonged baroreflex activation. Additional long-term studies are needed to provide greater insight into this controversy.…”
Section: Discussionmentioning
confidence: 94%
“…Our data confirm that even modest blood pressure increases are important to the acute regulation of the renal sodium excretion in the rat. In the absence of blood pressure changes, other mediators, such as RSNA and nNOS-derived NO, are operative and functionally important; studies in dogs and humans (3,27,28) have shown that marked natriuresis may result from acute salt loading, which does not affect mean arterial blood pressure at all. One of the conclusions of the present investigation, therefore, is that the neurohumoral control of renal excretion in the conscious rat should be studied by procedures that do not generate changes in renal arterial blood pressure, i.e., under conditions emulating the normal homeostatic regulation.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The changes in renal sodium excretion in response to changes in AP provide a link between the mechanisms regulating sodium excretion and those regulating AP. 1 Because glomerular filtration rate (GFR) and filtered sodium load are autoregulated over the same AP range, the mechanism of pressure natriuresis involves decreased tubular sodium reabsorption in response to increased AP; 6 however, the relative contributions of the various nephron segments responsible have not been fully defined.…”
mentioning
confidence: 99%